Die Option - Messner, Reinhold (Piper, 1989)
Die Option. Herausgegeben von Reinhold Messner. Piper-Verlag, München 1989. 272 Seiten, 29,80 Mark
Literaturverz. S. 269 - 270
Keywords: Option in Südtirol